IMPLEMENTASI PENDIDIKAN INKLUSIF BERBASIS KETERAMPILAN KERJA UNTUK MENINGKATKAN KESIAPAN KERJA MAHASISWA PENDIDIKAN VOKASIONAL TATA RIAS - Ririn Amaliah Putri Sarah; Suaida Suaida; Merdila Nuril Fahmi; Wirma Surya; Suci Fajrina; Syielvi Dwi Febrianty (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
This study is motivated by the suboptimal work readiness of students in Beauty Education, which tends to be dominated by technical skills and lacks development in social and professional aspects. The study aims to analyze the effectiveness of inclusive learning based on work skills in improving students’ work readiness. This research employed a quantitative approach with a quasi-experimental design using a pretest–posttest control group. The participants consisted of 60 students divided into an experimental group and a control group, with 30 students in each group. The instruments used included a work readiness questionnaire, observation sheets, and documentation. The research procedures involved pretest administration, implementation of inclusive learning based on work skills through diverse client simulations, task differentiation, and reflective learning activities, followed by posttest administration. Data analysis was conducted using normality testing (sig. > 0.05), homogeneity testing (sig. = 0.213), paired sample t-test, independent sample t-test, and N-Gain analysis. The results showed that the average work readiness score of the experimental group increased from 65.20 to 85.40, while the control group increased from 64.80 to 74.10. The t-test results indicated a significant difference between groups (p = 0.000 < 0.05). The N-Gain score for the experimental group was 0.58 (moderate–high category), while the control group obtained 0.27 (low–moderate category). The findings conclude that inclusive learning based on work skills is effective in comprehensively improving students’ work readiness across cognitive, affective, psychomotor, and social aspects. ABSTRAK Penelitian ini dilatarbelakangi oleh belum optimalnya kesiapan kerja mahasiswa Pendidikan vokasional tata rias yang masih didominasi aspek teknis dan kurang pada aspek sosial-profesional. Penelitian ini bertujuan untuk menganalisis efektivitas pembelajaran inklusif berbasis keterampilan kerja dalam meningkatkan kesiapan kerja mahasiswa. Penelitian menggunakan pendekatan kuantitatif dengan desain kuasi eksperimen pretest–posttest control group. Subjek penelitian berjumlah 60 mahasiswa yang dibagi ke dalam kelompok eksperimen dan kelompok kontrol, masing-masing 30 mahasiswa. Instrumen yang digunakan meliputi kuesioner kesiapan kerja, lembar observasi, dan dokumentasi. Tahapan penelitian meliputi pretest, pelaksanaan pembelajaran inklusif berbasis keterampilan kerja melalui simulasi klien beragam, diferensiasi tugas, dan refleksi pengalaman belajar, serta posttest. Analisis data dilakukan melalui uji normalitas (sig. > 0,05), uji homogenitas (sig. = 0,213), paired sample t-test, independent sample t-test, serta analisis N-Gain. Hasil penelitian menunjukkan bahwa rata-rata skor kesiapan kerja kelompok eksperimen meningkat dari 65,20 menjadi 85,40, sedangkan kelompok kontrol meningkat dari 64,80 menjadi 74,10. Hasil uji t menunjukkan perbedaan signifikan antar kelompok (p = 0,000 < 0,05). Nilai N-Gain pada kelompok eksperimen sebesar 0,58 (kategori sedang–tinggi), sedangkan kelompok kontrol sebesar 0,27 (kategori rendah–sedang). Simpulan penelitian ini adalah bahwa pembelajaran inklusif berbasis keterampilan kerja efektif dalam meningkatkan kesiapan kerja mahasiswa secara komprehensif pada aspek kognitif, afektif, psikomotor, dan sosial.